Estudio transversal de infección por malaria vivax en gestantes en la amazonía peruana durante los meses de junio - agosto del 2021 - Gomez Bergyer, Martin Antonio (2022)
Malaria susceptibility is increased during pregnancy. In semi-immune women, lifelong exposure to P. falciparum parasites has induced immunity that controls infection with common parasite phenotypes, such as parasites expressing PfEMP1 variants. that bind to CD36 on the endothelium of the peripheral vasculature. Therefore, the total biomass of the parasite may be low and difficult to diagnose with standard tools such as blood smear microscopy, even in the presence of significant placental infection. Furthermore, in the placenta, infected erythrocytes (IE) express the VAR2CSA variant of PfEMP1 to bind chondroitin sulfate A (CSA) but not other common endothelial receptors such as CD36 or ICAM-1. New mothers lack immunity to CSA-binding parasites and are highly susceptible to parasitaemia and chronic infections, making this group an important reservoir of infection in the community. During successive pregnancies, women may acquire antibodies against the CSA-binding IE and resistance to placental malaria, suggesting that a vaccine is feasible. Gestational malaria can cause maternal morbidity and mortality, intrauterine growth retardation, premature delivery, low body weight at birth and increased mortality of the newborn. In the Peruvian Amazon, malaria surveillance, in seasons of high transmission, with active detection of cases using light microscopy, increases the chance of detecting cases of malaria infection, the predominant species being Plasmodium vivax. Additional sociodemographic factors may also be responsible for the resurgence of malaria as a public health problem in Loreto, since in the rural areas surrounding Iquitos, the inhabitants live from agriculture, fishing, and logging. These activities involve camping in groups during the week and returning home on weekends, giving opportunity to different malaria endemic regions. Despite efforts, no significant progress has been made in reducing malaria cases in the pregnant population. This study has been developed with the purpose of identifying the prevalence of Plasmodium vivax malaria serology in pregnant women and its relationship with the parasitological study by thick film and/or blood smear. The results will allow us to increase public health recommendations in the Peruvian Amazon. Knowing the prevalence of malaria serology in pregnant women and its relationship with the parasitological study by thick smear and/or blood smear may have public health implications to implement campaigns to eliminate its main reservoir, the Anopheles mosquito, and malaria in pregnant women from the Peruvian Amazon.